Nutrition Value, Feed Efficiency and Species of Seagrass as a Feed of Wild Dugong (Dugong dugon) in Lingayan island, Tolitoli, Central Sulawesi - Nurdin, Muhammad Ardiansyah; Suprayogi, Agik; Satyaningtijas, Aryani Sismin; Darusman, Huda Salahuddin (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
Dugong are endangered herbivorous marine mammals, which one of the causes of extinction is degradation of seagrass as main feed of the dugong to survive. Aim of this study was to measure the quality of seagrass of wild dugong in Lingayan island, Central Sulawesi. The results showed proximat analysis value of Halophyla minor, Halodule uninervis and Cymodocea rotundata as seagrass species respectively showed values crude protein of 6.86%, 7.69% and 8.79%, crude fiber of 10.77%, 18.36% and 24.26 %, crude fat of 0.99%, 1.81 and 1.5%, calcium of 0.79%, 2.12% and 1.89%, phosphorus of 0.34%, 0.34% and 0.26 and gross energy of 163.4 cal / kg, 300.5 cal / kg and 319.5 cal / kg. Cymodocea rotundata is the best feed for dugong because it contains high energy of 319.5 cal/kg and high protein 8.79%, if compared with Halophyla minor of 1622 cal/kg) and Halodule uninervis of 3014 cal/kg) furthermore Cymodocea rotundata has a fairly high crude fat content of 1.44% which will increase fat levels under the skin (subcutaneous ) dugong as insulators of changing environmental conditions. High concentrations of fiber in Cymodocea rotundata 25.26% can help retain water as long as food passes in the intestine. The levels of nutrients in Cymodocea rotundata which found in Lingayan island deserve highest nutritious feed of dugong.